Determinants of Overweight or Obesity among Men Aged 20-59 Years: A Case-Control Study Based on the 2016 Ethiopian Demographic and Health Survey - Yohannes Tekalegn (Hindawi Limited, 2021)
Background. Evidence shows that overweight or obesity has become a major public health problem in both developed and developing countries. However, there are limited studies conducted to identify the risk factors of overweight or obesity in Ethiopia. Therefore, this study aimed to assess the determinants of overweight or obesity among men aged 20-59 years in Ethiopia. Methods. This study used the 2016 Ethiopian Demographic and Health Survey (EDHS) data. A case-control study was conducted based on the EDHS data; cases were men who were overweight or obese, depending on their body mass index, and controls were men with normal body mass index. Bivariate and multivariate binary logistic regression was performed to assess the determinants of overweight or obesity among the study participants. Results. A total of 610 cases and 2440 controls were included in this study. Men aged 30-39 years (adjusted odds ratio (AOR) = 2.2, 95% CI: 1.6-3.0) and ≥40 years (AOR = 3.4, 95% CI: 2.5-4.7) had higher odds of being overweight or obese compared to men aged 20-29 years old. The likelihood of overweight or obesity was significantly higher among married men (AOR = 1.5, 95% CI: 1.1-2.0), living in urban areas (AOR = 3.1, 95% CI: 2.1-4.4), those in the rich wealth quintile (AOR = 1.9, 95% CI: 1.2-2.9), and those with primary (AOR = 1.6, 95% CI: 1.1-2.3), secondary (AOR = 2.6, 95% CI: 1.7-3.9), and higher education (AOR = 3.6, 95% CI: 2.4-5.6). Additionally, men watching television at least once a week had higher odds (AOR = 1.5, 95% CI: 1.1-2.1) of being overweight or obese. Conclusion. Men in the higher wealth quintile, older age, married, higher educational status, watching television at least once a week, urban dwellers, residents of big cities such as Addis Ababa and Harari, and residents of low land like Afar were more likely to be overweight or obese. Therefore, it is essential to design strategies and programs to reduce or prevent overweight or obesity with a special focus on the identified risk factors.